2020
DOI: 10.1210/endocr/bqz044
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Hypothalamic Gene Expression and the Oxytocinergic System by Soybean Oil Diets in Male Mice

Abstract: Soybean oil consumption has increased greatly in the past half-century and is linked to obesity and diabetes. To test the hypothesis that soybean oil diet alters hypothalamic gene expression in conjunction with metabolic phenotype, we performed RNA sequencing analysis using male mice fed isocaloric, high-fat diets based on conventional soybean oil (high in linoleic acid, LA), a genetically modified, low-LA soybean oil (Plenish), and coconut oil (high in saturated fat, containing no LA). The 2 soybean oil diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 93 publications
1
11
0
Order By: Relevance
“…[33] In the present study, SO100 group was glucose intolerant after the supplementation period, while CO consumption did not affect glucose homeostasis. Studies have shown that SO has more diabetogenic effect than CO. [34][35][36] This is due to the difference in the composition of these oils (Table 1), CO is rich in saturated MCFA and SO has a high level of oleic acid, linoleic acid, and linolenic acid, [31] which can directly impact the dysregulation of gene expression in mice hypothalamus, such as gene coding for oxytocin, [34] which in turn plays an important role in glucose homeostasis. [37] In addition, we investigated obesity-related biomolecular markers, such as activation of inflammatory pathways and expression of the cytokines and chemokines in the epididymal adipose tissue, hypothalamus, and liver.…”
Section: Discussionmentioning
confidence: 99%
“…[33] In the present study, SO100 group was glucose intolerant after the supplementation period, while CO consumption did not affect glucose homeostasis. Studies have shown that SO has more diabetogenic effect than CO. [34][35][36] This is due to the difference in the composition of these oils (Table 1), CO is rich in saturated MCFA and SO has a high level of oleic acid, linoleic acid, and linolenic acid, [31] which can directly impact the dysregulation of gene expression in mice hypothalamus, such as gene coding for oxytocin, [34] which in turn plays an important role in glucose homeostasis. [37] In addition, we investigated obesity-related biomolecular markers, such as activation of inflammatory pathways and expression of the cytokines and chemokines in the epididymal adipose tissue, hypothalamus, and liver.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Deol et al. demonstrated a profound dysregulation of hypothalamic gene expression in mice fed soy oil-containing diet compared to control and coconut oil-containing diet with different proportions of fatty acid composition ( Deol et al., 2020 ). An increase in oxytocin expression and a decrease of oxytocin immunoreactivity were detected in the hypothalamus of mice fed diet containing soybean oil compared to mice fed control or coconut oil-containing diet, clearly demonstrating that quality of fat consumption impacts on brain neurochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…The Arg8-vasopressin kit has a sensitivity of 0.9 pg/mL in a dynamic range of 1.638–1,000 pg/mL. For the Enzo Life Sciences kits, samples underwent solid phase extraction using 200 mg C18 Sep-pak columns as previously described (Deol et al 2020 ). Plasma oxytocin and arginine vasopressin were quantified by interpolating absorbance or luminosity values, respectively, using a 4-parameter-logarithmic standard curve (MyAssays).…”
Section: Methodsmentioning
confidence: 99%